Effective tax rates and the “industrial policy” hypothesis: Evidence from Malaysia - Derashid, Chek; Zhang, Hao (Elsevier Science Inc., 2003)
Studies on effective tax rates (ETR) and firm size in the non-U.S. context are next to non-existent, with the Kim and Limpaphayom study (1998) being the sole exception. Moreover, no detailed analysis has been performed to study the link between industrial sectors and ETR.Based on a hand-gathered sample of Malaysian firms trading in the Kuala Lumpur Stock Exchange in 1990–1999, this paper examines the association between ETR and a set of possible factors using a regression analysis.There is evidence to suggest that manufacturing firms and hotels pay significant lower effective tax in Malaysia between 1990–1999. In addition, it appears that large Malaysian firms do not suffer a “political cost” as indicated by a negative and significant relation between firm size and ETR.Finally, more efficient Malaysian firms pay lower effective tax. The results are consistent with the “industrial policy” hypothesis developed in this paper based on an examination of the Malaysian context.These results from a large developing country (e.g., Malaysia) can be used to compare with existing results from a large developed country (e.g., U.S.).